1986
DOI: 10.1073/pnas.83.5.1295
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the radical species in compound ES of cytochrome c peroxidase altered by site-directed mutagenesis.

Abstract: Yeast cytochrome c peroxidase reacts with hydrogen peroxide to form an intermediate, compound ES, in which the heme iron atom is converted to a ferryl function (Fe4" =O) and a radical center is generated on a reversibly oxidizable amino acid residue of uncertain identity. As methionine-172 is a possible site of this radical, we have constructed specific variants of cytochrome c peroxidase in which methionine-172 is replaced by serine or cysteine. These mutants and the wild-type enzyme have been expressed in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…[12] The advent of site-directed mutagenesis helped resolve some of the uncertainty surrounding the identity of the CCP ES radical. Dave Goodin, Grant Mauk, and Michael Smith demonstrated that Met 172 could not be the site of this radical, [13] and measurements from Kraut’s laboratory on the CCP Trp 51 Phe mutant demonstrated that this residue was not the source of the radical signal. [14] The X-ray crystal structure of CCP ES identified a new possible locus for the radical site, near a cluster composed of the Met 230 , Met 231 , and Trp 191 sidechains, about 10 Å from the proximal side of the heme.…”
Section: Free Radicals In Proteinsmentioning
confidence: 99%
“…[12] The advent of site-directed mutagenesis helped resolve some of the uncertainty surrounding the identity of the CCP ES radical. Dave Goodin, Grant Mauk, and Michael Smith demonstrated that Met 172 could not be the site of this radical, [13] and measurements from Kraut’s laboratory on the CCP Trp 51 Phe mutant demonstrated that this residue was not the source of the radical signal. [14] The X-ray crystal structure of CCP ES identified a new possible locus for the radical site, near a cluster composed of the Met 230 , Met 231 , and Trp 191 sidechains, about 10 Å from the proximal side of the heme.…”
Section: Free Radicals In Proteinsmentioning
confidence: 99%
“…Protein-based radicals are essential to a variety of enzymatic systems [3], such as ribonucleotide reductases [4,5] and heme peroxidases [6][7][8][9][10][11][12]. Cytochrome c Oxidase (CcO), which catalyzes the reduction of oxygen to water, has been proposed to involve a protein-based radical [13][14][15] in its catalytic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Myoglobin [61][62][63][64][65][66][67][68][69][70] and its site-directed mutants [71,72], when oxidized to high oxidation states, are investigated as important protein models for compounds I and II. Cytochrome c peroxidase (CcP) was the first peroxidase for which a crystal structure became available [73], and was the first to be extensively studied by site-directed mutagenesis [74,75]. In contrast to HRP, the two-electron oxidized compound I analogue of CcP (also called compound ES) [47,[76][77][78] is red colored and contains a tryptophan cation radical [77,79,80] rather than a porphyrin p-cation radical.…”
Section: Introductionmentioning
confidence: 99%